Analisis Harga Saham dan Volume Perdagangan Saham Sebelum dan Sesudah Melakukan Stock Split (Studi Empiris pada Perusahaan Go Public Periode 2010-2015) - Fandi Ichwan Sidqi; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2017)
Capital market activity as one of the potential of the national economy increasingly puts its rolein developing the national economy. Several methods are used by IPOs for shares that investors maintaintheir stocks and shares glance that they can remain competitive in the world capital markets, one ofwhich is to implement a stock split.This study aimed to analyze the effect of the stock split on stock pricesand trading volumes. This type of research is a study that is included in the category event study or thestudy of events. Type of sampling using purposive sampling method. The sample in this study were 42companies that conduct a stock split in the period 2010-2015.The results of this study indicate that thereare significant differences between the stock price and trading volume before and after the stock split.Stock split is still a policy that affect stock prices and trading volumes. Results were obtained byanalyzing secondary data using the data normality test, different test, and Wilcoxon signed ranktest.Based on this, the researchers suggest though stock split is still a significant effect, but the stock splitdid not ensure that the market will react as expected the company, as a result of this study showed thatthe activity of the stock split does not guarantee that the average stock trading volume will increaseaccordingly with purpose. Therefore, issuers are advised paying attention to other factors in decidingpolicies stock split.